As mulheres existem: teoria feminista, estudos de gênero e história das mulheres na formação de professores de História - COSTA, Camila Frota da (Universidade Federal do Pará, 2023)
This paper aims the analysis of History teachers' education regarding the feminist theories, Women's History and gender studies which are fundamental to the teacher's qualifications concerning the school environment, permeating through diverse family structures, gender and sexual orientation, race, and social classifications. The History Degree's Educational Projects of The Federal University of Pará, taking both Belém and Ananindeua's campi, are the main sources of this research, having been used to evaluate if there is a commitment to surpassing the teaching methodologies based on a "unique History", traditional, linear, ethnocentric and male-centered core. Giving the recent attacks towards the teaching freedom in schools by conservative movements and having been convinced of the necessity of a teacher's formation revision, it has been considered by the authors that teachers must be prepared to dodge these curbings and provide an evermore inclusive and emancipatory education. This paper has been written in a time which the No-party School Movement, anachronicaly, has grown in the politics' scenario in Brazil, with evident reflexes in BNCC, once the document has been emptied of contents regarding gender, diversity and sexuality. From these premises above mentioned, an intervention has been proposed in the pre-Columbian America subject, in which the educational project has been structured in way that women authors and feminist works are favored. The classes taught during this subject have been analysed and are part of this work. this experience has inspired the production of a podcast series about History teaching, feminism and Women's History, having History teachers willing to rethink their practices from these themes' perspective as the target audience. The series, in a propositional form, is the second produt from this paper.